Дух: ("Стержень спирали", книга 2) / Эдуард Вайнштейн - Вайнштейн Эдуард С. (Ключ, 1997)
Экземпляры: КХ (19980115) / Инвентарный номер: 1028045 / Цена: 24000.00 / Сис.шифр: 87 / Авт.знак: В 14 / ГРНТИ: 02 / ББК: 87